2017
DOI: 10.1371/journal.pone.0172267
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological assessment of the severity of dengue epidemics in French Guiana

Abstract: BackgroundDengue fever is the most important arboviral infection that affects humans, particularly in tropical and subtropical regions. Here, we provide the first comprehensive overview of the severity of dengue epidemics in French Guiana.Methodology/Principal findingsWe monitored hospitalized cases between 2008 and 2013. Detailed clinical features and biological parameters were collected on a daily basis from all cases. Among the 1,356 cases, 216 (16%) were classified according to the WHO 2009 classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
(21 reference statements)
2
15
0
1
Order By: Relevance
“…It is possible that these patients may have not needed hospitalisation, consistent with previous findings in the literature . As dengue outbreaks often present substantial spatial and temporal clustering , misclassifying dengue patients as severe may result in unnecessary congestion of the healthcare system .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these patients may have not needed hospitalisation, consistent with previous findings in the literature . As dengue outbreaks often present substantial spatial and temporal clustering , misclassifying dengue patients as severe may result in unnecessary congestion of the healthcare system .…”
Section: Discussionmentioning
confidence: 99%
“…Flamand C et al report that children aged <7 years comprised >20% of their study population, and prevalence was less in infants (4.0%) while Dias JJ Júnior reported that 66.0% of the study population wih severe dengue were children <15 years. 9,10 These reports indicate that case of fever in pediatric patients needs careful evaluation. Report from Malaysis is indicating a declining trend among pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 serotypes of DENV circulate in FG in endemic-epidemic form. In the past 10 years, there has been an increase in the number of DENV outbreaks and hospitalized cases [ 3 , 4 ]. Thus far, A aegypti mosquitoes have been the sole vector implicated in these outbreaks, and A albopictus have not been actually reported in FG [ 5 ].…”
mentioning
confidence: 99%